Administración de proyectos con Excel usando PERT/CPM (ING) - Azofeifa Zamora, Carlos E. (2002)
The PERT/CPM technique, used in the administrative science, helps to prove and control the tasks that are interrelated by means the resolution of the project benefits of the technique applied. Also PERT/Cost technique is used to check the project’s cost.